2021
DOI: 10.1128/msystems.00500-21
|View full text |Cite
|
Sign up to set email alerts
|

Surface-Shaving Proteomics of Mycobacterium marinum Identifies Biofilm Subtype-Specific Changes Affecting Virulence, Tolerance, and Persistence

Abstract: Mycobacteria are naturally resilient, and mycobacterial infections are notoriously difficult to treat with antibiotics, with biofilm formation being the main factor complicating the successful treatment of tuberculosis (TB). The present study shows that nontuberculous Mycobacterium marinum ATCC 927 forms submerged- and pellicle-type biofilms with lichen- and ribbon-like structures, respectively, as well as persister cells under the same conditions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(22 citation statements)
references
References 94 publications
4
12
0
Order By: Relevance
“…The minimum duration for killing (MDK) assay was performed as previously described [48]. Briefly, F0804-1219 and F1092-1799 were dissolved in dimethyl sulfoxide (Sigma Aldrich, St. Louis, MO) prior to being added on top of the Mmr biofilm cultures at the desired concentrations (8 µl/well).…”
Section: Minimum Duration For Killing (Bioluminescence)mentioning
confidence: 99%
“…The minimum duration for killing (MDK) assay was performed as previously described [48]. Briefly, F0804-1219 and F1092-1799 were dissolved in dimethyl sulfoxide (Sigma Aldrich, St. Louis, MO) prior to being added on top of the Mmr biofilm cultures at the desired concentrations (8 µl/well).…”
Section: Minimum Duration For Killing (Bioluminescence)mentioning
confidence: 99%
“…demonstrated that the administration of nebulized cellulase enhanced the antimycobacterial activity of isoniazid and rifampicin in infected mice, supporting the role of biofilms in phenotypic drug tolerance ( Chakraborty et al., 2021 ). Savijoki et al. (2021) also reported that increased celA1 synthesis in M. marinum prevents biofilm formation and leads to reduced rifampicin tolerance.…”
Section: Discussionmentioning
confidence: 93%
“…Cording in vitro is typically studied using mycobacterial biofilms grown as pellicles at the air–liquid interface; an exception is cording described in rotary cell culture [ 43 ]. In contrast to pellicle biofilms, submerged mycobacterial biofilms have a non-corded, lichen-like morphology [ 39 ]. Cording occurs intracellularly (i.e., within the host) and is thought to impair host immune surveillance [ 44 ].…”
Section: Discussionmentioning
confidence: 99%